Remittances Vis-A-Vis Foreign Direct Investment - A Case Study - Rizvi, Saima (Indian Journal of Finance, 2009)
Remittance is sending money, cheques to a recipient at a distance. NRI Remittances have been playing a pivotal role in economic growth of India just as across the world. India enjoys the status of receiving the highest remittances in the world. With an increasing number of Non Resident Indians (NRIs) living overseas, either for work or having settled there , flows in country have certainly grown dramatically in the past few years. The figures have gone up touching US$23bn in 2006, up from US$ 2 bn a year in the late 1980s. After FDI, remittances have emerged as the largest external capital source for developing nations like India. Amount of NRI remittances have been exceeding FDI inflows in India for last few years.The case study attempts to analyze the fact that though in India a lot of importance is given to Foreign Direct Investment and Foreign Institutional Investors (FIIs), but remittances are also contributing in a big way to the economy. Growth in remittances is contributed by many factors including the growth of financial institutions and companies such as Western Union, HSBC Bank, IndusInd Bank, Dhanalakshmi Bank and so on. The case study is based on secondary data collected from various newspapers, magazines, journals, books and websites.